EFFORTS TO PREVENT VIOLENCE AGAINST CHILDREN THROUGH THE DEVELOPMENT OF MODULE FOR MIDWIFE PROFESSION - Lisdha Yantie; Nita Arisanti; Hadi Susiarno (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Violence against children during the COVID-19 pandemic has increased drastically. One of the efforts to prevent violence against children is through dissemination of information to the midwife through the use of the media, namely the CENDANA module for Midwives on the prevention of child violence. This research aimed to find out the results of expert validation of the CENDANA module and analysed the implementation effect of the module on increasing the knowledge of Midwives.Methods: Uses quantitative methods with descriptive design and pretest posttest with control group design. The topics were obtained from previous research, then expert validation was carried out consisting of material experts, education experts, and media experts. Next is the module trial, with 60 respondents in the intervention group and control group. The intervention group was given a modules, and the control group was given leaflets. Data were analyzed using the Mann Whitney test. The research instrument was in the form of a questionnaire.Results: The measurement after the intervention, it showed that there was a significant difference in the post data, the increase data, and the increase percentage of knowledge in the two treatment groups (p<0.05). The increase percentage amount of knowledge scores in the intervention group was 54.4%, while in the control group there was no increase (0%). Conclusion: It was found that the CENDANA’s module was said to be feasible, and there was an implementation effect of the module on increasing the knowledge of Midwives about prevention of violence against children.